2008
DOI: 10.2215/cjn.01640408
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-induced Nephrogenic Diabetes Insipidus

Abstract: Background and objectives: Polyuria, polydipsia, and nephrogenic diabetes insipidus have been associated with use of psychotropic medications, especially lithium.Design, setting, participants, & measurements: The impact of psychotropic medications on urinary concentrating ability and urinary aquaporin 2 (AQP2) excretion was investigated after overnight fluid deprivation, and over 6 h after 40 g of desmopressin (dDAVP), in patients on lithium (n ‫؍‬ 45), compared with those on alternate psychotropic medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 28 publications
1
89
0
15
Order By: Relevance
“…This drug not only blocks sodium entry via ENaC, but also inhibits lithium entry into collecting duct principal cells. Amiloride partially restores the urinary concentrating ability, and this is associated with increased urinary AQP2 excretion 10 .…”
Section: Treatment Of Lithium-induced Nephrogenic Diabetes Insipidusmentioning
confidence: 97%
See 3 more Smart Citations
“…This drug not only blocks sodium entry via ENaC, but also inhibits lithium entry into collecting duct principal cells. Amiloride partially restores the urinary concentrating ability, and this is associated with increased urinary AQP2 excretion 10 .…”
Section: Treatment Of Lithium-induced Nephrogenic Diabetes Insipidusmentioning
confidence: 97%
“…The most prevalent form of lithium-induced renal injury is impaired urinary concentrating ability 10 , which can be detected about eight weeks after lithium initiation 11 . In a study involving 1,172 patients on chronic lithium therapy, Boton et al 11 found that impairment of urinary concentrating ability was present in at least 54% of 1,105 unselected individuals.…”
Section: Lithium-induced Tubular Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amiloride blocks ENaC-mediated Li entry into renal cells and ameliorates this effect. 6 Li-induced NDI may become irreversible in some subjects after treatment for more than 2-10 years.…”
Section: Nephrogenic Diabetes Insipidusmentioning
confidence: 99%